Multinuclear Solid‐State Magnetic Resonance as a Sensitive Probe of Structural Changes upon the Occurrence of Halogen Bonding in Co‐crystals. Issue 36 (26th July 2013) - Widdifield, Cory M.; Cavallo, Gabriella; Facey, Glenn A.; Pilati, Tullio; Lin, Jingxiang; Metrangolo, Pierangelo; Resnati, Giuseppe; Bryce, David L.
Abstract Although the understanding of intermolecular interactions, such as hydrogen bonding, is relatively well‐developed, many additional weak interactions work both in tandem and competitively to stabilize a given crystal structure. Due to a wide array of potential applications, a substantial effort has been invested in understanding the halogen bond. Here, we explore the utility of multinuclear (13C, 14/15N, 19F, and 127I) solid‐state magnetic resonance experiments in characterizing the electronic and structural changes which take place upon the formation of five halogen‐bonded co‐crystalline product materials. Single‐crystal X‐ray diffraction (XRD) structures of three novel co‐crystals which exhibit a 1:1 stoichiometry between decamethonium diiodide (i.e., [(CH3)3N+(CH2)10N+(CH3)3][2 I−]) and different para‐dihalogen‐substituted benzene moieties (i.e., p‐C6X2Y4, X=Br, I; Y=H, F) are presented. 13C and 15N NMR experiments carried out on these and related systems validate sample purity, but also serve as indirect probes of the formation of a halogen bond in the co‐crystal complexes in the solid state. Long‐range changes in the electronic environment, which manifest through changes in the electric field gradient (EFG) tensor, are quantitatively measured using 14N NMR spectroscopy, with a systematic decrease in the 14N quadrupolar coupling constant (CQ) observed upon halogen bond formation. Attempts at 127I solid‐state NMR spectroscopy experiments are presented and variable‐temperature 19F NMR experiments are used to distinguish between dynamic and static disorder in selected product materials, which could not be conclusively established using solely XRD. Quantum chemical calculations using the gauge‐including projector augmented‐wave (GIPAW) or relativistic zeroth‐order regular approximation (ZORA) density functional theory (DFT) approaches complement the experimental NMR measurements and provide theoretical corroboration for the changes in NMR parameters observed upon the formation of a halogen bond.